Factors Influencing Positive Birth Experiences of First-Time Mothers - Lena Nilsson; Tina Thorsell; Elisabeth Hertfelt Wahn; Anette Ekström (Nursing Research and Practice)
Objectives. The objective of this study was to describe first-time mothers’ experiences and reflections of their first birth. Study Design. This study is a part of a larger study which was carried out in southwestern Sweden in 2008. A qualitative method with content analysis was chosen for this study. The unit of data was 14 written narratives from the first-time mothers. Results. The theme “To be empowered increases first-time mothers’ chances for a positive birth experience” crossed over into all the three categories: “To trust the body and to face the pain,” “Interaction between body and mind in giving birth,” and “Consistency of support.” Conclusion. In order to feel confident in their first childbirth, the women wanted to be confirmed and seen as unique individuals by the professionals and their partner. If professionals responded to the individual woman’s needs of support, the woman more often had a positive birth experience, even if the birth was protracted or with medical complications.